Manajemen Konflik Dalam Gereja Mula-Mula: Tafsir Kisah Para Rasul 2:41-47 - Frans Paillin Rumbi (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2019)
Frans Paillin Rumbi, Conflict Management in The Early Church: Interpretation of the Acts 2:41-47. The main question put forward in this study is that in the early church there was no conflict? On that basis, the writer tries to find answers by using library research methods with the reader response interpretation approach. The result seems to be that the congregation was originally formed in the midst of conflict. Furthermore, in the early days they were confronted with internal and external conflicts. Internal conflicts include inner conflicts related to their waiting for the Kingdom of God and inner conflicts of individualistic and materialistic. The choice between prioritizing one's own welfare or having to share with others. To overcome the various conflicts that arise, they try to process it by first consistently building alliances on the basis of the work of the Holy Spirit. Furthermore, they developed a lifestyle based on the spirit of repentance and desire to renew the way of life, practicing the teachings of the Lord Jesus and the Apostles by promoting solidarity with others and controlling individualistic and materialist attitudes, building intensive communication in order to create mutual understanding and mutual understanding.